2021
DOI: 10.24018/ejmed.2021.3.3.808
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Occurrence and Percentage Distribution of Rh C, Rh c, Rh E and Rh e Blood Group Amongst Pregnant Women Attending Antenatal Clinic in Port Harcourt, Nigeria

Abstract: Background: The Rhesus (Rh) blood group is one of the most complex blood groups in humans comprising mainly of Rh D, C, c, E and e. However, only Rh D is routinely screened for in Nigeria despite the fact that other Rh antigens are clinically significant and can cause haemolytic disease of the newborn and delayed haemolytic transfusion reactions. Aim: The aim was to determine the frequency distribution of Rh C, c, E and e blood groups among pregnant women attending antenatal clinic in Port Harcourt, Nige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Similar findings have been observed in various studies in Africans. 19 , 20 However, similar results are observed in a few white populations and about 2.9% of the Indian population. 1 , 21 , 22 These findings are not similar to those obtained by Sarkar, 23 Makroo et al 24 Prinja et al 25 and Basu et al, 4 who observed the order of prevalence to be CDe/CDe, CDe/cDe, CDe/cDe, and cDe/cDE.…”
Section: Discussionsupporting
confidence: 75%
“…Similar findings have been observed in various studies in Africans. 19 , 20 However, similar results are observed in a few white populations and about 2.9% of the Indian population. 1 , 21 , 22 These findings are not similar to those obtained by Sarkar, 23 Makroo et al 24 Prinja et al 25 and Basu et al, 4 who observed the order of prevalence to be CDe/CDe, CDe/cDe, CDe/cDe, and cDe/cDE.…”
Section: Discussionsupporting
confidence: 75%
“…16 Two studies conducted in Nigeria on pregnant women reported a notable difference in Rhc antigenic frequencies of 100% and 60.7%, respectively. 17,18 However, these results were based on serological testing and not confirmed by molecular typing. This signifies the importance of molecular testing for the exact characterization of Rhc antigen to resolve these contrasting serological results.…”
Section: Discussionmentioning
confidence: 99%
“…Hackney, 19 has also reported similar observation after a review of 102 pregnancies managed at the Ohio State University from 1967 to 2001 for anti-c isoimmunization and concluded that Anti-c isoimmunization might cause significant fetal and newborn haemolytic disease Distribution of Rh Antigens with respect to previous transfusion history in studied participants showed that 6 (5.0%) for Rh-C, 15 (12.5%) for Rh-c, 6 (5.0%) for Rh E and 17 (14.2%) for Rh-e respectively among studied participants who have had previous transfusion while those with no history of previous transfusion showed 16 (12.5%), 92 (76.6%), 41 (34.2%) and 93(77.5%) for Rh-C, Rh-c, Rh-E and Rh-e respectively in the studied population. Research done by Christian,11 indicated that allo-immunization due to Rh antibodies may occur as a result of blood transfusion. However, this was not observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…An antibody of Rh E is also capable of causing haemolytic transfusion reaction and haemolytic disease of the newborn. 11 The Rhe is not as frequent as the Rh E antigen and its antibodies have been seen to cause haemolytic transfusion reaction and haemolytic disease of the newborn. 10 To prevent allo-immunization, women of reproductive age are given red cell transfusions compatible for Rh antigens such as C, c, D, E and e. This requirement may also be indicated for transfusiondependent patients who receive regular red cell transfusions to prevent allo-immunization against the Rhesus antigens.…”
Section: Introductionmentioning
confidence: 99%